2018
DOI: 10.3390/s18124231
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Hybrid Steel and FRP-Reinforced Concrete—ECC Composite Columns under Reversed Cyclic Loading

Abstract: Fibre-reinforced polymer (FRP) is used widely in concrete structures owing to its noncorrosive, light-weight, nonmagnetic, and high tensile-strength properties. However, the FRP-reinforced concrete flexural member exhibits low ductility owing to the linear–elastic property of FRP reinforcement. Hybrid steel—FRP-reinforced concrete members exhibit good strength and ductility under flexure owing to the inelastic deformation of steel reinforcement. The existing investigations have focused on the mechanical behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Currently, in regard to modern engineering structures, carrying capacity and deformation properties are in great demand [1]. In the past two decades, fiber reinforced polymer (FRP) composites have been widely applied in civil engineering construction, because of their several advantages, such as higher corrosion resistance, higher strength to weight ratio, and superior durability in aggressive environments [2].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, in regard to modern engineering structures, carrying capacity and deformation properties are in great demand [1]. In the past two decades, fiber reinforced polymer (FRP) composites have been widely applied in civil engineering construction, because of their several advantages, such as higher corrosion resistance, higher strength to weight ratio, and superior durability in aggressive environments [2].…”
Section: Introductionmentioning
confidence: 99%
“…Fiber-reinforced polymer (FRP) tubes, which are characterized by light weight, high strength, corrosion resistance, easy processing, and fatigue resistance, were first applied to military facilities in the US, and then to the construction field by British engineers [1,2]. An FRP-confined concrete column is a composite component formed by wrapping FRP on the outside of the concrete column.…”
Section: Introductionmentioning
confidence: 99%
“…FRC and ECC are efficient cement-based composites that can compensate for the drawbacks of quasibrittleness of conventional concrete and has better structural performance than conventional concrete [23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Zhang et al [24][25][26] conducted the seismic performance tests of steel fiberreinforced concrete (SFRC) locally reinforced hollow piers at the potential plastic hinges, which showed that the application of SFRC can improve the ductility and bending performance of the piers.…”
Section: Introductionmentioning
confidence: 99%
“…e proposed model estimated the shear behavior of the SFRC members well. e test results by Li et al [31][32][33][34][35] indicated that the use of ECC materials in the connection plastic region as a replacement of conventional concrete and partial replacement of transverse reinforcement can significantly enhance the joint shear resistance, energy absorption capacity, and cracking response. erefore, it has been shown that FRCs materials represent a feasible alternative for use in earthquake-resistant structures [33].…”
Section: Introductionmentioning
confidence: 99%